Engaging Māori with qualitative healthcare research using an animated comic. (10th December 2020) - Kearns, Ciléin; Baggott, Christina; Harwood, Matire; Reid, Alice; Fingleton, James; Levack, William; Beasley, Richard
Abstract: This article reports an effective strategy for recruiting patients with asthma to a qualitative study using an animated comic advertised on social media. An ad spend of NZ$432 on Facebook resulted in 101 study enquiries, and 27 participants taking part in the focus groups, of which 16 (56%) were Māori, the Indigenous Peoples of New Zealand. Representation of Māori amongst participants was over five times higher than their proportion in the local population (9.7%), resulting in data fulfilling the principle of equal explanatory power, an approach to research which can help advance Māori health development and address inequity. The success of this campaign is of particular interest for health researchers in New Zealand where Māori continue to be disproportionately affected by poorer health outcomes compared with non-Māori, particularly those with asthma. Approaches that better engage and support participation of under-represented communities in clinical research are of wider global interest. We reflect on the recruitment strategy and outcomes within a Kaupapa Māori framework, explore how this can be applied more widely in healthcare, and suggest direction for future study and implementation. Lay summary We designed an animated comic to advertise a study for patients with asthma. This was shared locally with a Facebook ad. The approach was highly engaging with the public, and resulted in rapid recruitment. Interestingly, participation of Māori (the Indigenous People of New Zealand) was over five times higher than their proportion in the local population. Māori have poorer health outcomes and increased barriers to healthcare access compared with non-Māori, particularly those with asthma. Approaches which can engage and support under-represented communities to participate in clinical research are of wider global interest. In this article, we reflect on the recruitment strategy and outcomes, and suggest direction for future study and implementation.